2023
DOI: 10.3390/ma16217059
|View full text |Cite
|
Sign up to set email alerts
|

The Microstructures and Deformation Mechanism of Hetero-Structured Pure Ti under High Strain Rates

Shuaizhuo Wang,
Haotian Yan,
Dongmei Zhang
et al.

Abstract: This study investigates the microstructures and deformation mechanism of hetero-structured pure Ti under different high strain rates (500 s−1, 1000 s−1, 2000 s−1). It has been observed that, in samples subjected to deformation, the changes in texture are minimal and the rise in temperature is relatively low. Therefore, the influence of these two factors on the deformation mechanism can be disregarded. As the strain rate increases, the dominance of dislocation slip decreases while deformation twinning becomes m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Wang et al [ 1 ] investigated the microstructures and deformation mechanism of hetero-structured pure Ti under various high strain rates. The results indicated that as the strain rate increased, the dominance of the dislocation slip decreased, while deformation twinning became more prominent.…”
Section: Dynamic Mechanical Properties and Constitutive Model Of Mate...mentioning
confidence: 99%
“…Wang et al [ 1 ] investigated the microstructures and deformation mechanism of hetero-structured pure Ti under various high strain rates. The results indicated that as the strain rate increased, the dominance of the dislocation slip decreased, while deformation twinning became more prominent.…”
Section: Dynamic Mechanical Properties and Constitutive Model Of Mate...mentioning
confidence: 99%